When the EU takes the field. Innovative forms of regulatory enforcement in the fisheries sector. Issue 4 (19th May 2022) - Eliantonio, Mariolina; Cacciatore, Federica
ABSTRACT: One of the main weaknesses of the EU and causes of citizens' disaffection is its alleged scarce effectiveness in achieving its targets among various policy sectors. This, among other reasons, is due to member states' (MS) lack of compliance or uneven implementation performance, which, in turn, results from the traditional share of tasks, according to which the EU institutions adopt policies, while the MS implement them and enforce them. After many and reiterated actions by the EU, aiming to foster better and more complete compliance to EU law through soft measures and incentives to MS, another trend is emerging, by which the EU is gradually taking on direct enforcement competences in a growing number of policy sectors. Moreover, the ways through which the EU is taking the field in the enforcement phase are many and diverse, ranging from direct full enforcement powers to differently shared and networked roles with the MS and the other actors involved. In such evolving governance, a crucial role is played by EU agencies, established ad hoc or attributed new tasks to deal with enforcement issues.Arguing that such verticalization of the enforcement powers is an expanding trend, we take the fisheries sector as a case study. Among the Common Fisheries Policy, indeed, this phenomenon is already gaining traction and displays a variety of new configurations of powers. We find that verticalized enforcement takes on different shapes, depending on the specific sub-phase of the enforcement process, In addition, we provide insights on how enforcement mechanisms of the Common Fisheries Policy work in practice.